Neuroendocrine Control of Energy Metabolism - Panzica, Giancarlo; Gotti, Stefano; Collado Guirao, Paloma (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The control of energy metabolism is a central event for cell, organ, and organism survival. There are many control levels in energy metabolism, although in this Special Issue, we concentrated on the neuroendocrine control which is operated through specialized neural circuits controlling both food intake and energy expenditure. Due to the explosion of obesity and associated diseases, the subject of this Special Issue is of particular interest today.